An evaluation of community perceptions on the greater Letaba livelihoods for the community of Mariveni, Limpopo Province - Lekganyane, Mmamare Alice (My University, 2025)
The perceptions of the community towards rivers as a source of livelihood are quite crucial not only for the derived socio-economic livelihoods but also for the effective management of rivers as perception is central to how the local people perceive the river in terms of water quality, water quantity, and related land use changes. Moreover, it is important to promote their sustainability to ensure that they continue to provide social, environmental, and economic benefits to the communities. This study aimed to evaluate how Mariveni community members view the Greater Letaba River as a source of sustainable livelihoods. To collect data, a mixed-method approach was used involving a survey questionnaire which was administered to 98 households that were sampled randomly. Observation as a data collection technique was supplemented to note aspects such as activities around the rivers and other aspects that the respondents did not mention during the surveys. The senses of sight hearing, taste, and smell were used to determine water quality and water quantity. Almost 80% of the respondents indicated that they rely on the river as a resource. Nonetheless, many respondents indicated that the water quantity was reduced due to a decrease in rainfall and farm irrigation among others. The water quality was reported to be poor, and this was said to have been caused by the dumping of garbage in the river, farming activities, disposal of waste such as diapers, waste from animals, chemicals from farming activities, and sewage pipes draining into the river.Perceptions differed with the majority being those who indicated that there was no change. The respondents indicated that there was an increase in the frequency with which they visited clinics due to people becoming ill more regularly due to poor water quality. Fishing was no longer feasible which led to reduced related business and food security. There was also a reduction in recreational activities such as swimming. People had to travel to those households that sank boreholes to buy water at a high price and this also had an impact on the time spent with their families. Those who had gardens along the river could not irrigate which also hurt the recreational activities. The conclusion is that the community values the Greater Letaba River as a source of their livelihood. The recommendations include raising awareness through local structures such as the councilor through the Integrated Development Plan (IDP) for recognition of the importance of the Greater Letaba as a valuable resource. The sinking of boreholes and dam construction were also some of the interventions recommended by the community but also but the researcher.
Thesis (M.Sc. (Geography)) -- University of Limpopo, 2025
Keywords: Sustainable Development; Mariveni community; Water scarcity; Water quality; Climate change; Water pollution; Livelihood; Perceptions; Water -- Pollution; Climatic changes; Water quality -- South Africa -- Limpopo; Sustainable development -- South Africa -- Limpopo